2017
DOI: 10.1016/j.scitotenv.2017.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil chemical properties in an organic farm in Croatia

Abstract: Soil pH, electrical conductivity (EC), organic matter (OM), available phosphorus (AP), and potassium (AK) are some of the most important indicators of soil fertility. These soil parameters are highly variable in space and time, especially in agricultural areas, with implications for crop production. The aim of this work was to study the spatial variability of pH, EC, OM, AP and AK using kriging and co-kriging methods in the Rasa River Valley (Croatia). As co-variates for each variable we considered the distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 90 publications
(88 reference statements)
3
45
0
1
Order By: Relevance
“…Phosphorus is an essential element for plant growth, and application of P-fertilizers is needed to overcome the deficiency of phosphorus in arable soils 43 . Spatial autocorrelation was low for soil AP in farmlands 44 . The random distribution of phosphorus indicated that fertilization history might still have impacts on soil phosphorus at the initial restoration stage after agricultural abandonment.…”
Section: Discussionmentioning
confidence: 89%
“…Phosphorus is an essential element for plant growth, and application of P-fertilizers is needed to overcome the deficiency of phosphorus in arable soils 43 . Spatial autocorrelation was low for soil AP in farmlands 44 . The random distribution of phosphorus indicated that fertilization history might still have impacts on soil phosphorus at the initial restoration stage after agricultural abandonment.…”
Section: Discussionmentioning
confidence: 89%
“…Soil properties exhibited low (only soil pH) to moderate (rest of soil properties) variability with <10, 10 to 100 and > 100% of CV values indicating variability to the extent of low, moderate, and high degree, respectively (Nielsen & Bouma, ). Bogunovic et al () reported low, medium, and high variability for pH, organic matter, and EC, respectively in soils of Rasa river valley of Croatia. Behera and Shukla () reported low (for pH and EC) to moderate (for SOC content) variability in Indian acid soils.…”
Section: Resultsmentioning
confidence: 99%
“…Since soils are highly heterogeneous and distribution of soil properties (Behera & Shukla, ; Bogunovic, Pereira, & Brevik, ) and Zn, Fe, Cu, and Mn concentrations in soils varies spatially (Fageria et al, ; Pereira & Ubeda, ; Shukla et al, ; Shukla et al, ), blanket application of these nutrients leads to imbalanced addition of Zn, Fe, Cu, and Mn (Ferguson, Lark, & Slater, ). Thus, the balanced and site‐specific management through varied nutrient application rate holds the key for economically sustainable agricultural production (Behera et al, ; Tesfahunegn, Tamene, & Vlek, ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to different climatic variables, parent materials, soil texture, topography, and vegetation types, nutrients are distributed heterogeneously in soils and their contents vary highly both spatially and temporally, especially in forest areas (Wang et al, 2009;Liu et al, 2013b;Bogunovic et al, 2017;Guan et al, 2017). In recent years, several studies have dealt with the spatial variability of soil pH (Fu et al, 2010;Liu et al, 2013a), organic carbon (C) (Lal, 2005;O'Rourke et al, 2015;, electrical conductivity (EC) (Bogunovic et al, 2017), and N and P contents (Wang et al, 2009;Fu et al, 2010;Liu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Unsus-tainable forest management practices decrease soil nutrient content and organic matter, change soil structure, and restrict ecosystem-scale productivity (Martín-Peinado et al, 2016;Ade et al, 2018). The application of N-rich fertilizers results in soil acidification in forestlands (Guo et al, 2010), reducing the availability of essential elements for plant growth (Zhang et al, 2005), and producing potential risks for human health (Martín-Peinado et al, 2016;Bogunovic et al, 2017). Furthermore, frequent and intense soil irrigation in plantations may increase salt concentration in surface soil (Liu et al, 2013a;Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%